2017
DOI: 10.1370/afm.2100
|View full text |Cite
|
Sign up to set email alerts
|

Physician Support of Smoking Cessation After Diagnosis of Lung, Bladder, or Upper Aerodigestive Tract Cancer

Abstract: PURPOSE Smoking cessation after a diagnosis of lung, bladder, and upper aerodigestive tract cancer appears to improve survival, and support to quit would improve cessation. The aims of this study were to assess how often general practitioners provide active smoking cessation support for these patients and whether physician behavior is influenced by incentive payments. METHODSUsing electronic primary care records from the UK Clinical Practice Research Datalink, 12,393 patients with incident cases of cancer diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 25 publications
0
28
0
1
Order By: Relevance
“…27,[45][46][47] Os urologistas e os médicos de família, pressionados pelos constrangimentos do tempo de consulta, sentem que a promoção de cessação é pouco eficiente e desapontante, o que pode justificar o pouco investimento na prática clínica diária. [46][47][48][49] Este estudo apresenta algumas limitações, para além das referidas anteriormente, que deverão ser tidas em conta na apreciação das conclusões: 1) o desenho transversal do estudo prejudica a atribuição de causalidade dos dados 2) os doentes não participantes eram mais velhos e do sexo feminino, duas características associadas à ausência de tabagismo -este facto poderá ter condicionado uma sobrevalorização da taxa de fumadores 3) os dados da história tabágica foram baseados nas entrevistas, sem a confirmação bioquímica da abstinência, existindo o risco da subestimação do número de fumadores ativos 50,51 4) o tempo entre o diagnóstico e a entrevista não foi homogéneo, o que acarreta um risco inerente de viés de memória.…”
Section: Discussionunclassified
“…27,[45][46][47] Os urologistas e os médicos de família, pressionados pelos constrangimentos do tempo de consulta, sentem que a promoção de cessação é pouco eficiente e desapontante, o que pode justificar o pouco investimento na prática clínica diária. [46][47][48][49] Este estudo apresenta algumas limitações, para além das referidas anteriormente, que deverão ser tidas em conta na apreciação das conclusões: 1) o desenho transversal do estudo prejudica a atribuição de causalidade dos dados 2) os doentes não participantes eram mais velhos e do sexo feminino, duas características associadas à ausência de tabagismo -este facto poderá ter condicionado uma sobrevalorização da taxa de fumadores 3) os dados da história tabágica foram baseados nas entrevistas, sem a confirmação bioquímica da abstinência, existindo o risco da subestimação do número de fumadores ativos 50,51 4) o tempo entre o diagnóstico e a entrevista não foi homogéneo, o que acarreta um risco inerente de viés de memória.…”
Section: Discussionunclassified
“…for promoting smoking cessation. 9) However, a recent study showed that after diagnosis, physicians provide less smoking cessation support to cancer patients than to patients with CVD, 10) resulting in a lower smoking cessation rate among cancer patients (36.7% vs.…”
Section: Disease Diagnosis and Associated Events Have Been Consideredmentioning
confidence: 99%
“…10) After receiving a diagnosis or being hospitalized for CVD, approximately 50% of smokers quit smoking according to a systematic review, 11) whereas nearly 30 to 40% of smokers quit smoking after cancer diagnosis in large-scale studies. 10,12,13) However, these studies focusing on cancer diagnosis 10,12,13) may have included participants with an early stage of cancer who might therefore have been less motivated to quit smoking. 9) If cancer treatment takes a longer time, resulting in long-term hospitalization or sick leave, patients may take smoking cessation more seriously and be more motivated to quit smoking.…”
Section: Disease Diagnosis and Associated Events Have Been Consideredmentioning
confidence: 99%
See 1 more Smart Citation
“…General practitioners are less likely to support smoking cessation in patients with lung, bladder, and upper aerodigestive tract cancer than coronary heart disease, and patients with cancer are less likely to stop smoking. 43 In a study of 870,319 community health center patients, Holderness et al find a very interesting pattern of large and unequal reductions in the rate of uninsurance in 10 states that expanded Medicaid and 6 states that did not. 44 This issue continues the new Annals feature on Innovations in Primary Care.…”
mentioning
confidence: 99%